1989
DOI: 10.1093/oxfordjournals.aje.a115341
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms Among Mexican Americans: The Hispanic Health and Nutrition Examination Survey

Abstract: This paper presents findings on depressive symptomatology among 3,118 Mexican-American adults who participated in the Hispanic Health and Nutrition Examination Survey (HHANES). In 1982-1984, the National Institute of Mental Health Center for Epidemiologic Studies Depression Scale was administered to Mexican Americans aged 20-74 years as part of the HHANES examination component. Respondents reported in either English or Spanish on both the presence and persistence of depressive symptoms during the week prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
1
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(133 citation statements)
references
References 8 publications
2
129
1
1
Order By: Relevance
“…14 Dementia was diagnosed according to Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition criteria when scores in tests of recent and late memory and of another cognitive function were Ͻ1 SD of the normative control group, relatives scored Ͼ57 in SS-IQCODE, and activities of daily living were impaired. The final diagnosis was always reached by an experienced neurologist (T.d.S.)…”
Section: Diagnosis Of Poststroke Dementia and Cognitive Statusmentioning
confidence: 99%
“…14 Dementia was diagnosed according to Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition criteria when scores in tests of recent and late memory and of another cognitive function were Ͻ1 SD of the normative control group, relatives scored Ͼ57 in SS-IQCODE, and activities of daily living were impaired. The final diagnosis was always reached by an experienced neurologist (T.d.S.)…”
Section: Diagnosis Of Poststroke Dementia and Cognitive Statusmentioning
confidence: 99%
“…Early epidemiological studies of Latinos found that rates of disorder vary by subgroup ( Moscicki, Locke, Rae, & Boyd, 1989 ;Narrow, Rae, Moscicki, Locke, & Regier, 1990 ), with new immigrants tending to have lower rates of disorder.…”
Section: Access To Latinos In the United Statesmentioning
confidence: 99%
“…These include: de creased fiber consumption (30); decreased breast feeding (25); increased use of cigarettes (48); increased alcohol consumption-especially in younger women 04, 39, 58,60,76) and driving under the influence of alcohol (22); and increased use of illicit drugs (1,75,80,82,86,92). Some studies have also documented that depressive symptomatology increases with ac culturation (13,42,52,67,79,96), although the relationship between depression and acculturation remains controversial (86).…”
Section: Health Status and Acculturationmentioning
confidence: 99%